Toxicity of sulfide to early life stages of wild rice (Zizania palustris). (6th April 2017) - Fort, Douglas J.; Todhunter, Kevin; Fort, Troy D.; Mathis, Michael B.; Walker, Rachel; Hansel, Mike; Hall, Scott; Richards, Robin; Anderson, Kurt
Abstract: The sensitivity of wild rice ( Zizania palustris ) to sulfide is not well understood. Because sulfate in surface waters is reduced to sulfide by anaerobic bacteria in sediments and historical information indicated that 10 mg/L sulfate in Minnesota (USA) surface water reduced Z. palustris abundance, the Minnesota Pollution Control Agency established 10 mg/L sulfate as a water quality criterion in 1973. A 21‐d daily‐renewal hydroponic study was conducted to evaluate sulfide toxicity to wild rice and the potential mitigation of sulfide toxicity by iron (Fe). The hydroponic design used hypoxic test media for seed and root exposure and aerobic headspace for the vegetative portion of the plant. Test concentrations were 0.3, 1.6, 3.1, 7.8, and 12.5 mg/L sulfide in test media with 0.8, 2.8, and 10.8 mg/L total Fe used to evaluate the impact of iron on sulfide toxicity. Visual assessments (i.e., no plants harvested) of seed activation, mesocotyl emergence, seedling survival, and phytoxicity were conducted 10 d after dark‐phase exposure. Each treatment was also evaluated for time to 30% emergence (ET30), total plant biomass, root and shoot lengths, and signs of phytotoxicity at study conclusion (21 d). The results indicate that exposure of developing wild rice to sulfide at ≥3.1 mg sulfide/L in the presence of 0.8 mg/L Fe reduced mesocotyl emergence. Sulfide toxicity was mitigated by the addition of Fe at 2.8 mg/L and 10.8 mg/L relative to the control value of 0.8 mg Fe/L, demonstrating the importance of iron in mitigating sulfide toxicity to wild rice. Ultimately, determination of site‐specific sulfate criteria taking into account factors that alter toxicity, including sediment Fe and organic carbon, are necessary. Environ Toxicol Chem 2017;36:2217–2226. © 2017 SETAC